An examination of the psychometric properties of the Patient Health Questionnaire-9 (PHQ-9) in a Multiracial/ethnic population in the United States - Shaff, Jaimie; Kahn, Geoffrey; Wilcox, Holly C. (Frontiers in Psychiatry, 2024)
Depression and suicide are significant public health issues. The Patient Health Questionnaire-9 (PHQ-9) is commonly used to assess for symptoms of depression, but its psychometric properties within multiracial and multiethnic populations remains uncertain. In a study involving 1,012 English-speaking multiracial/ethnic participants from the United States, the PHQ-9 showed strong internal consistency (α = 0.93) and supported a one-factor structure. No measurement variance was observed between Non-White and White/Non-White multiracial/ethic subgroups. PHQ-2, with a cutoff of ≥3, identified fewer depression cases than PHQ-9 (32% vs. 40%), with sensitivities of 75%-99% and specificities of 74%-96%; a cutoff of ≥2 missed fewer cases. Item performance of the ninth PHQ-9 question, addressing suicidal ideation, varied across generations with younger generations more likely to endorse suicidal ideation at any level of symptom severity. The findings suggest the PHQ-9 demonstrated adequate reliability within a population of multiracial/ethnic adults in the US; however, the use of the 9 th item of the PHQ-9 may not be adequate for identifying individuals at risk for suicidal thoughts and/or behaviors, particularly for older multiracial and multiethnic adults. The lower sensitivity of the PHQ-2 with a ≥3 cutoff suggests a cutoff of ≥2 may be preferable to miss fewer cases of depression.